Quality of Sleep and its associated risk factors among maintenance Hemodialysis patients in Pakistan. - Mahjabeen Yaseen, Shagufta Naqvi, Amna Saleem, Rida Nasreen, Rida Imran, Aysha Mahmood (Journal of Rawalpindi Medical College, 2021)
ABSTRACT Background: Chronic Kidney disease patients on maintenance hemodialysis have a poor and compromised life. Sleep quality and pattern is frequently impaired and leads to psychological and physical issues among them. The aim of this study is to determine the quality of sleep and its associated risk factors among maintenance hemodialysis patients. Materials and Methods: This Observational cross sectional study was carried out at the Hemodialysis units of Al Mustafa Medical Institute and Alamgir International Welfare Trust from March to August 2019.A total of 156 patients above 18 years of age were recruited in the study. Data was collected regarding demographic characteristics (age, gender, education, marital status, and employment), dialysis characteristics (duration, shift) renal disease characteristics (duration, etiology), smoking status, comorbidities like Cardiovascular Diseases, Hypertension, Diabetes Mellitus, Hepatitis B positive and Hepatitis C positive status. Sleep quality was assessed using Pittsburg Sleep Quality Index (PSQI) and sleep quality score was calculated according to that. Those with a scores of < 5 or 5 indicate good sleep quality, and scores of >5 indicate poor sleep quality. Data was analyzed using the Statistical Package for the Social Sciences version 25.0 Results: Total 156 patients undergoing hemodialysis completed the questionnaire. Majority of the participants (52.9%) were male while 47.1% were female. Out of 140 participants 89(57.1) had a poor quality of sleep while 67(42.9) had a good quality of sleep. A significant association was found between poor quality of sleep and increasing age, smoking and hepatitis B positive status (P<0.05). Conclusion: Sleep quality is impaired in patients on maintenance hemodialysis. Associated risk factors were age, hepatitis B, smoking. Key words: Sleep Quality, maintenance hemodialysis, Pittsburg Sleep Quality Index.